Tanzania - In touch with livestock challenge [interview with Almasi Ndemo Tipaa] - International Livestock Research Institute (International Livestock Research Institute, 2021)
This video is one of a series putting farmers' perspectives at the centre of a global discussion. The ‘In Touch with Livestock Challenge’ initiative opens constructive dialogues on sustainable farming in relation to the global goals on climate, biodiversity and food security.